A Call for Mental Health Treatment in Incarcerated Settings with Transgender Individuals. Issue 5 (19th October 2020) - Tadros, Eman; Ribera, Erik; Campbell, Olivia; Kish, Halle; Ogden, Taylor
Abstract: The U.S. correctional system has become the epicenter for public health and mental health crisis. This article discusses literature documenting incarcerated transgender individuals' mental health treatment. The severity of mental illness treatment issues within the system amongst transgender and other LGBTQ + individuals, clearly displays the need for interventions tailored to this population. Recommended interventions are centered around post traumatic response and cater to those who exist in marginalized populations with consideration given to the significance of family strain and support. Overall, there is a need for a shift in mindset and available services to treat incarcerated transgender individuals.